2010
DOI: 10.2214/ajr.09.3828
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Focal Pure Ground-Glass Opacities on High-Resolution CT Images: Clinical Significance in Patients With Lung Cancer

Abstract: The size of most focal pure GGOs associated with lung cancer did not change during the follow-up period. Most of the small number of lesions histologically diagnosed were atypical adenomatous hyperplasia or bronchioloalveolar carcinoma. These data justify the therapeutic strategy of resecting the primary tumor without therapeutic intervention in the remaining focal pure GGOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
3
20
1
Order By: Relevance
“…The 5-year OS and RFS proportions of our data were satisfactory and all the patients with multifocal pure GGOs remained alive for 5 years without recurrence, similarly to several previous studies [5,14,15].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The 5-year OS and RFS proportions of our data were satisfactory and all the patients with multifocal pure GGOs remained alive for 5 years without recurrence, similarly to several previous studies [5,14,15].…”
Section: Discussionsupporting
confidence: 89%
“…Several studies addressing this topic have reported similar results, demonstrating a favorable prognosis [5,[12][13][14][15]. The 5-year OS and RFS proportions of our data were satisfactory and all the patients with multifocal pure GGOs remained alive for 5 years without recurrence, similarly to several previous studies [5,14,15].…”
Section: Discussionsupporting
confidence: 89%
“…However, at least one invasive focus measuring more than 5 mm in greatest dimension must be present. In a series of 39 patients with multifocal ground glass lesions and negative lymph nodes, Gu et al [35 & ] recently reported a 100% overall survival after anatomic resection of the dominant tumor and wedge resection of all other accessible ground glass opacities (GGO), which is in line with data from previous studies [36][37][38][39]. The average percentage of the lepidic pattern in LPA was recently reported to be 50% (range: 40-85%) with acinar (81%) and papillary (17%) as the predominant accompanying invasive components [26 && ].…”
Section: Lepidic Predominant Adenocarcinomasupporting
confidence: 76%
“…With developments in CT examination technology, such as the application of low鈥恉ose mass screening and HRCT, GGO is now more commonly detected clinically . The five鈥恲ear survival rate has been reported at almost 100% for AAH, AIS, and MIA patients; however, the long鈥恡erm survival rate of patients with invasive adenocarcinoma remains poor .…”
Section: Discussionmentioning
confidence: 99%